Imagem país na perspectiva dos turistas: o caso do Peru - Ortiz, Victor Jesus Escobedo (2016)
The objective of this study was to identify the key aspects of the country image definition from the perspective of tourists, in a way that it can contribute to the creation of a country brand. The idea emerged with the interest of analyzing the concept of country brand and for that it was necessary to understand the concepts of country image and destination image. This work defines the country's image as all mental representations that the consumer has to process information about a place through long-time experiences. The destination image has the same principle of the country image, but can refer to other levels of geographical limits, as a city, a defined region and country. With the literature review on the country image was obtained 11 categories, which were used in the analysis phase of field research. As a way to identify the contents that define the concept, data were collected through interviews, using as a focal country Peru. 20 people was interviewed over 18 years who visited Peru as a tourist during the last six years, the ZMET method was used for interviews, since this technique is used to obtain or capture unconscious thoughts, attitudes and perceptions of respondents. From the results obtained by analysis of content, it is concluded that not all dimensions in theory is confirmed as first order, that is, there are dimensions that can be grouped to obtain a better representation of the concept. Therefore it proposes the following categories to assess the image of a country for tourism sector: 1) Socioeconomic and political environment; 2) General infrastructure; 3) Infrastructure for tourism, recreation and leisure; 4) Culture, history and arts; 5) Natural resources; 6) Technology; and 7) Country character. The other dimensions shown in theory are proposed as sub-dimensions of the indicated dimensions.